Carrying on the family's legacy: Male heirs and firm innovation - Chen, Shu; Ying, Sammy Xiaoyan; Wu, Huiying; You, Jiaxing (Journal of Corporate Finance, 2021)
We predict that entrepreneurs are more likely to have a long-term orientation to their decision making if they have male heirs, because traditionally sons, not daughters, have been expected to carry on the family business. Our results support this prediction. Specifically, we find that when entrepreneurs have at least one son, have more sons, and have a firstborn son, their firms are more innovative. The results are robust to a battery of robustness tests, including alternative measures of innovation, instrumental variable approach, and Heckman two-step correction for selection bias. Our further analyses show that the positive association between male heirs and firm innovation is stronger for entrepreneurs with a greater son preference and is weaker for entrepreneurs who more impacted by the one-child policy.